1996
DOI: 10.1074/jbc.271.29.17536
|View full text |Cite
|
Sign up to set email alerts
|

The Homeobox Gene

Abstract: The Pem gene encodes an atypical homeodomain protein, distantly related to Prd/Pax family members, that we demonstrate is regulated in a complex transcriptional and post-transcriptional manner. We show that the rat Pem genomic structure includes three 5-untranslated (5-UT) exons and four coding exons, three of which encode the homeodomain. Several alternatively spliced transcripts were identified, including one that skips an internal coding exon, enabling this mRNA to express a novel form of the Pem protein. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…We also considered the possibility that IVS1 and IVS2 preferentially leak out of the nucleus during RNA preparation in vitro because they are smaller than Pem pre-mRNAs. To test this notion, we examined the localization of Pem IVS3, as it is much larger (2.4 kb) than the other Pem introns (25). We found that IVS3 was present in the cytoplasmic fraction at a level approximately equal to that in the nuclear fraction, when an equal amount of RNA from each fraction was loaded (Fig.…”
Section: Detection Of Splicedmentioning
confidence: 99%
See 4 more Smart Citations
“…We also considered the possibility that IVS1 and IVS2 preferentially leak out of the nucleus during RNA preparation in vitro because they are smaller than Pem pre-mRNAs. To test this notion, we examined the localization of Pem IVS3, as it is much larger (2.4 kb) than the other Pem introns (25). We found that IVS3 was present in the cytoplasmic fraction at a level approximately equal to that in the nuclear fraction, when an equal amount of RNA from each fraction was loaded (Fig.…”
Section: Detection Of Splicedmentioning
confidence: 99%
“…In the present communication, we report on the fate, localization, and stability of spliced introns from the Pem homeodomain gene, a mammalian gene that contains typical mammalian introns ranging in length from ϳ0.2 to 2.4 kb (25,26). Unlike the other genes from which spliced introns have been studied, the Pem gene is not expressed in a cell type-specific manner.…”
mentioning
confidence: 96%
See 3 more Smart Citations